2011
DOI: 10.4250/jcu.2011.19.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Circadian Blood Pressure Variation and Left Atrial Function Using Strain Imaging

Abstract: BackgroundNon-dippers were reported as showing different left atrial function, compared to dippers, but no study to date investigated the changes in the left atrial function according to the diurnal blood pressure pattern, using tissue Doppler and strain imaging.MethodsForty never treated hypertensive patients between 30 and 80 years of age were enrolled in this study. Patients were classified as non-dippers when, during night time, they had a blood pressure decrease of less than 10%. Strain of the left atrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…However, this is not the first study revealing the effect of dipper and nondipper status of essential hypertension in the terms of LA phasic function. In contrast to our study, Park et al 16 showed that both the reservoir and booster pump functions of the left atrium were increased in nondippers, when evaluated with strain and strain rate measured by Color Doppler tissue imaging. These findings were consistent with the results from measurements of the LA phasic volumes, as reported previously.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this is not the first study revealing the effect of dipper and nondipper status of essential hypertension in the terms of LA phasic function. In contrast to our study, Park et al 16 showed that both the reservoir and booster pump functions of the left atrium were increased in nondippers, when evaluated with strain and strain rate measured by Color Doppler tissue imaging. These findings were consistent with the results from measurements of the LA phasic volumes, as reported previously.…”
Section: Discussioncontrasting
confidence: 99%
“…However, conventional echocardiography seems to be inadequate for detecting subclinical LA dysfunction. 21 In another study, the LA global strain and strain rates were significantly lower in an NDHT group. 17 Several studies have suggested that both the strain and strain rate are correlated inversely with age and LA diameter in healthy individuals, and the LA strain rate decreases before LA enlargement and LV hypertrophy develop in hypertensive patients.…”
Section: Correlation Analysismentioning
confidence: 90%
“…20 A study of the LA strain and strain rate showed that the atrial reservoir and pump functions were impaired more in NDHT patients. 21 In another study, the LA global strain and strain rates were significantly lower in an NDHT group. 18 In parallel with this previous study, we observed significant differences in LA strain between dippers and nondippers, although there were no differences in tissue velocity between the two groups.…”
Section: Correlation Analysismentioning
confidence: 90%
“…Blood pressure (BP) follows a circadian rhythm with 10–15% lower values during the night than during the day [7]. Daytime BP is more closely related to target organ damage than nighttime BP [8,9].…”
Section: Introductionmentioning
confidence: 99%